Increasing Creativity in Early Childhood Through Illustrated Stories for Students - "Ain, Miratul; Sandi Ramdhani; Nur Adiyah Yuliastri (Indonesian Journal of Innovation in Education Research, 2025)
This research aims to determine the increase in children's creativity through picture stories. This research is classroom action research. The subjects in this research were students from group B1 PAUD Harapan Bangsa, Jabon, Selong Blanak Village, first semester of the 2023/2024 academic year. The number of students in group B1 PAUD Harapan Bangsa is 31 children. This research is collaborative between researchers, school principals, and accompanying class teachers. Data is collected through observation and documentation. The validity of the data was checked by triangulation. Data was analyzed descriptively qualitatively. The results of this research show that there is an increase in children's creativity through picture stories, namely pre-cycle creativity of 12.90%, cycle I creativity of 45.16% and cycle II creativity of 74.19%. Increasing children's creativity through picture stories is also supported by several indicators, namely creative reactions, long attention spans, self-organization/self-confidence, linking ideas/telling stories, developing imagination and adding new vocabulary. Apart from that, success in increasing creativity is also supported by supporting methods, including providing time to explore and providing very good motivation. The conclusion of this research is that picture stories can increase children's creativity